FEASIBILITY STUDY OF LORA BASED CONTROLLER FOR DRIP IRRIGATION SYSTEMS USING MULTI-HOP STAR TOPOLOGY NETWORK - Usmonov, Maksudjon; Asretdinova, Lobar (Innovative Development in Educational Activities, 2023)
The use of drip irrigation systems has become widespread in recent years, but controlling them on a large scale can be difficult. One solution to this problem is to set up a wireless sensor and actuator network (WSAN). However, using wireless technology in agriculture can be challenging, as it requires long battery life, long-range capabilities, and low cost. Recently, various technologies and protocols have been developed to address these challenges, such as LoRa, a proprietary wireless modulation technology. The LoRaWAN network protocol, which is built on top of LoRa, has been studied as a solution. However, this paper suggests a simpler and more cost-effective protocol specifically designed for controlling drip irrigation systems. The project described in this paper includes the implementation of hardware and software for wireless nodes and the development of a GUI app for controlling drip irrigation systems.